MATH SOLVE

3 months ago

Q:
# Jenn claims that because log(1) + log(2) + log(3) = log(6), then log(2) + log(3) + log(4) = log(9).Is she correct? Explain how you know.

Accepted Solution

A:

Answer:No, she is not correctStep-by-step explanation:Hi there!In the first case it works because of this logarithm property:log (a·b) = log a + log bLet´s see:log (6) = log(1) + log(2) + log(3)because 6 = 1 · 2 · 3So, instead log(6) we can write:log(1 · 2 · 3)And by the property of logarithm written above:log(6) = log(1 · 2 · 3) = log(1) + log(2) + log(3)In the second case:9 ≠ 2 · 3 · 4Then:log(9) ≠ log(2 · 3 · 4)Thuslog(9) ≠ log (2) + log(3) + log(4)Have a nice day!